Intestinal macrophages and their interaction with the enteric nervous system in health and inflammatory bowel disease. (12th August 2018) - Meroni, Elisa; Stakenborg, Nathalie; Viola, Maria Francesca; Boeckxstaens, Guy E.
Abstract: Over the past decades, there has been an increasing understanding of cellular and molecular mechanisms that mediate modulation of the immune system by the autonomic nervous system. The discovery that vagal nerve stimulation (VNS) attenuates endotoxin‐induced experimental sepsis paved the way for further studies investigating neuro‐immune interaction. In particular, great attention is now given to intestinal macrophages: several studies report the existence of both intrinsic and extrinsic neural mechanisms by which intestinal immune homoeostasis can be regulated in different layers of the intestine, mainly by affecting macrophage activation through neurotransmitter release. Given the important role of inflammation in numerous disease processes, such as inflammatory bowel disease (IBD), cholinergic anti‐inflammatory mechanisms are under intense investigation both from a basic and clinical science perspective in immune‐mediated diseases such as IBD. This review discusses recent insights on the cross‐talk between enteric neurons and the immune system, especially focusing on macrophages, and provides an overview of basic and translational aspects of the cholinergic anti‐inflammatory response as therapeutic alternative to reinstall immune homoeostasis in intestinal chronic inflammation.